PENGARUH LINGKUNGAN TEMPAT TINGGAL DAN SIKAP SISWA TEHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS X IPA SMA SUNGGUMINASA GOWA - Abdul Hadi; Rizky Ramadhana; Andi Tenriawaru (Almeera Education, 2023)
This study aims to determine the effect of the living environment and students' attitudes towards mathematics learning outcomes of SMA Sungguminasa Gowa students. The type of research